Primary Ewing's sarcoma of vulva: A case report and a review of the literature. Issue 3 (29th October 2012) - Che, Shao‐Min; Cao, Pei‐Long; Chen, Hong‐Wei; Liu, Zi; Meng, Du
Abstract Ewing sarcomas/peripheral primitive neuroectodermal tumors (ES/pPNET) are extremely rare in the vulva. A review of the literature reveals only 14 previously reported possible cases. Here we reported a case of primary extraskeletal Ewing's sarcoma (EES) of the vulva in a 37‐year‐old woman. Characteristic histologic features of ES/pPNET were present in this case, including a monomorphic population of small round blue cells with cytoplasmic glycogen confirmed by periodic acid‐Schiff, membrane staining with CD99 and nuclear staining with FLI‐1. After surgery, the patient was found to have pulmonary metastasis and then received six cycles of polychemotherapy. She is still alive with stable disease after 1 year of follow up. Our findings underline the crucial role of immunohistochemical techniques in the differential diagnosis of small round cell tumors in these unusual locations. We also give a summary about the clinical and pathological features of the primary ES/pPNET in the vulva reported previously in the literature.